Religious minorities in islamic legal traditions - Vikør, Knut S. (Religious minorities online, 2024)
Islam accepts the presence of certain non-Muslim groups, like Jews and Christians, in the Muslim state, under certain conditions. Islamic legal scholars discussed at length which religious groups should come under this permission and what the required conditions were. These dhimmī groups had the same protection of the state for their life and property as did the Muslim subjects but also had to show a level of submission under the Muslim order. Many of these legal and religious demands for humbleness were regularly ignored, so a fluctuating set of rules known as the ‘Pact of ʿUmar’ was at repeated intervals called upon to keep the dhimmīs in line. Under the Ottoman Empire, the system was formalized into religious communities known as millets, which lasted until the onset of modernity in the 19th and early 20th centuries.